(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The posterior coccyx joints play a crucial role in the structural integrity and functionality of the human spine. Despite their importance, clinical understanding of these joints, particularly in the context of coccydynia or coccygeal pain, remains a subject of ongoing exploration. This article aims to provide a comprehensive analysis of the clinical anatomy of the posterior coccyx joints, shedding light on their intricate structures, potential clinical implications, and current research trends.